2016
DOI: 10.1039/c6ib00179c
|View full text |Cite
|
Sign up to set email alerts
|

Mapping lung tumor cell drug responses as a function of matrix context and genotype using cell microarrays

Abstract: Carcinoma progression is influenced by interactions between epithelial tumor cells and components of their microenvironment. In particular, cell-extracellular matrix (ECM) interactions are known to drive tumor growth, metastatic potential, and sensitivity or resistance to therapy. Yet the intrinsic complexity of ECM composition within the tumor microenvironment remains a barrier to comprehensive investigation of these interactions. We present here a high-throughput cell microarray-based approach to study the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Multiple groups have attempted to capture the complexity of the microenvironment and test therapeutic sensitivity to drug treatments. For example, tumor cells have been cultured in different matrices to identify ECM combinations driving lung cancer 49,52 . Work done by such groups has given great insights into individual heterotypic interactions, however, these studies have been conducted using cell lines in an artificially created environment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups have attempted to capture the complexity of the microenvironment and test therapeutic sensitivity to drug treatments. For example, tumor cells have been cultured in different matrices to identify ECM combinations driving lung cancer 49,52 . Work done by such groups has given great insights into individual heterotypic interactions, however, these studies have been conducted using cell lines in an artificially created environment.…”
Section: Discussionmentioning
confidence: 99%
“…Then cell cycle, mitosis, ECM-receptor interaction and kinase activity, DNA binding were found closely correlated with the effect of ILK in EGFR-TKIs resistance. As they have been known, the cell cycle [25,26], ECM-receptor interaction [27,28], mitosis [29], were identified typically activated in cancer drug resistance, suggesting that ILK played a crucial role in EGFR-TKIs resistance of lung SqCC via these pathways. GO analysis also found that cell cycle and mitosis were the important signaling pathways involved in ILK knockout in EGFR-TKIs resistance.…”
Section: Discussionmentioning
confidence: 97%
“…The ‘cell cycle’, ‘oocyte meiosis, ‘ECM-receptor interaction’, ‘protein kinase activity’ and ‘DNA binding’ were identified to be closely associated with the effects of ILK on EGFR-TKI resistance. As the cell cycle ( 32 , 33 ), ECM-receptor interaction ( 34 , 35 ) and mitosis ( 36 ) have been identified to be activated in cancer drug resistance, ILK may serve a crucial role in the EGFR-TKI resistance of lung SqCC via these pathways. GO analysis results also demonstrated that ‘mitotic cell cycle’ and ‘mitosis’ were important signaling pathways involved in EGFR-TKI resistance in ILK-knockout cells.…”
Section: Discussionmentioning
confidence: 99%